Institutions and Asia's development: The role of norms and organizational power - Mushtaq H. Khan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The role of institutions in Asian development has been intensely contested since Myrdal's Asian Drama, with later contributions from institutional economics and developmental state theory. Despite much progress, the dominant approaches do not agree about the institutions that matter nor do they explain why similar institutions delivered such different results across countries. Cultural norms and informal institutions clearly matter but the appropriate norms did not already exist in successful countries; they evolved over time. The distribution of holding power across different types of organizations, the "political settlement", can explain the diversity of experiences and help to develop more effective policy.
Keywords: B52; L52; O17; O25; O43; 330; institutions; organizations; political settlements; norms; industrial policy; development